The impact of professional identity on teachers’ professional well-being: The mediating role of social support - Zhang, Haiying; Xie, Sen (Journal of Asian Scientific Research, 2025)
This study explores how professional identity affects professional well-being, examining whether social support mediates between the two variables. The convenience sampling method was adopted. A total of 1,321 valid data points were selected from five undergraduate institutions in Hebei Province. This article refers to the three scales and uses SPSS 24.0 and AMOS 24.0 software to analyze the data. Professional identity positively impacts both professional well-being and social support. Social support has a positive impact on professional well-being and plays a partial mediating role. There is a significant relationship among the variables, and social support partially mediates the relationship between professional identity and professional well-being. The sampling scope is limited to some undergraduate institutions in Hebei Province, which may affect the generalizability of the research. It provides valuable practical guidance for enhancing professional well-being, such as strengthening teachers’ professional identity and optimizing social support.